ETR 300 : Vintage Car Accessories Enterprise / Hasnizal Hawari ... [et al.] - Hawari, Hasnizal; Jaimi, Mohd Noor Ikhwan; Azhar, Ahmad Saiful; Junus, Mohd Hafiz; Abdul Halim, Khairul Izwan (2002)
Vintage Car Accessories Enterprise was established in 1st January 2002 which was located at no.8 Jalan Mawar 1 Aman Jaya , 08000 Sungai Petani Kedah. Our organization is formed in terms of partnership agreement, which total contribution, by partners RM 44,500and RM 80,000 from the Affin Finance. This Vintage Car Accessories business is a potential business to choose because the limited sources of antique car accessories such as Volkswagen, Mini Austin and etc. Besides that, the number of antique car fans has increase prove by the numbers of Vintage Car Club in Malaysia and event doing by Malaysian Government such as BUG FEST MALAYSIA 2001 (refer to appendix). Usually in this event and gathering activity the owner of the car want the best condition for their car to participate in exhibition and competition. We only want to display top quality of vintage accessories car that represent the best of what our company has to offer. We surely believe that we can succeed in this business fields because we provide variety of antique car model to compete with our competitor. The scope of our potential buyers also widen due to the behaviors of antique car owner who want the best for their car so we can attract the buyers not only from Kedah also in Penang ,Perlis and Perak. Furthermore, we have a good relationship with Vintage car club in order to get information about the interest of members club and their activity.